FINITE INTEGRALS PERTAINING TO A PRODUCT OF SPECIAL FUNCTIONS (Global Journal of Science Frontier Research, 2011)
An attempt has been made to establish an integral concerning the product of generalized Lauricella function and two H-function of several complex variables (Srivastava and Panda [4,5]) By giving suitable values to the parameters, the main integral reduces to F function. Mainly we are using the series representation of H-function given by Olkha and Chaurasia [2,3].
Keywords: Multivariable H-function; H-function in Series form; Lauricella function; Jacobi polynomial; KampE9; de FE9; riet function